Retrograde Angiography to Detect Dropped Thrombus in Mechanical Thrombectomy. Issue 5 (October 2022) - Aoki, Kazuaki; Miura, Yoichi; Toma, Naoki; Suzuki, Yume; Fujimoto, Masashi; Shiba, Masato; Yasuda, Ryuta; Suzuki, Hidenori
Objective: The risk of embolization to distal territory or to new territory in mechanical thrombectomy remains a major issue despite advancements in technological device. This condition can be caused by a large and firm dropped thrombus without passing through a guiding catheter during stent retriever or aspiration catheter withdrawal. This report introduced a novel technique referred to as retrograde angiography to detect dropped thrombus. Methods: The retrograde angiography to detect dropped thrombus technique is a kind of retrograde angiography that consists of a contrast medium injection via a distal microcatheter and aspiration through an inflated balloon-guiding catheter. This method was used to detect dropped thrombus at the balloon-guiding catheter tip when back flow was blocked from the balloon-guiding catheter after stent retriever or aspiration catheter withdrawal. We retrospectively reviewed four consecutive patients who underwent the retrograde angiography to detect dropped thrombus technique during mechanical thrombectomy for acute ischemic stroke due to large vessel occlusion in the anterior circulation between January 2018 and January 2021. Results: Three of four patients had dropped thrombus, which was diagnosed with the technique and retrieved completely with subsequent procedures while maintaining the balloon-guiding catheter inflated. None of the patients experienced embolization to distal territory/embolization to new territory, and a successful reperfusion was achieved in all four cases. Conclusions: The retrograde angiography to detect dropped thrombus is a technique to detect a dropped thrombus at the balloon-guiding catheter tip and allows us to retrieve it with subsequent mechanical thrombectomy procedures while maintaining the balloon-guiding catheter inflated and it may be useful for reducing the risk of embolization to distal territory/embolization to new territory.